Guideline-based Development of Quality Indicators for Prevention and Management of Postpartum Hemorrhage. Issue 3 (September 2016) - Woiski, M.D.; Scheepers, H.C.; Liefers, J.; Lance, M.; Middeldorp, J.M.; Lotgering, F.K.; Grol, R.P.; Hermens, R.P.
Abstract : ( Acta Obstet Gynecol Scand. 2015;94:1118–1127) Postpartum hemorrhage (PPH) is a major cause of maternal mortality worldwide, and it has been reported that many mothers suffering from hemorrhage received substandard care. Two recent studies have shown that 30% to 90% of women with PPH received care that is less than optimal, while a third study has shown that hospitals with a fetal maternal specialist experienced a lower rate of PPH. Research has also shown that a lack of training and education among health care providers could play a significant role in the development of severe hemorrhage. The authors of this paper developed a series of quality indicators to evaluate whether providers are adhering to the optimal guidelines when caring for patients with PPH.